Supermarket Energy Use in the UK. (March 2019) - Kolokotroni, Maria; Mylona, Zoi; Evans, Judith; Foster, Alan; Liddiard, Rob
Abstract: Recent data of energy consumption by supermarkets in the UK are presented and compared with existing benchmarks in the UK and data from other countries. It is shown that energy intensity has been reduced in large supermarkets (>750m 2 ) in recent years which is consistent with reductions in other countries due to installation of energy efficient technologies for all sub-systems (refrigeration, HVAC, lighting and building). Data for small supermarkets is not segregated in available databases; the presented modelling study, using a calibrated thermal model of a small supermarket, shows the interdependency of sub-systems, location and ratio of displayed products, which can inform system selection.